"A urbanização do tratamento da hanseníase" - Andrade, Vera Lucia Gomes de (1995)
In Brazil, the leprosy Control Program is presently showing some loss of quality in the care of patients of urban areas. In this regard, the study of the endemic in these areas is of importance, being of value the integration of all aspects of the control program that have some connection tothe understanding of the deterioration of the endemic and its social consequences. The purpose of this paper is to present some suggestions to the formulation of interventions to each conditions. Taking into consideration that decentralization of the knowledge of the object to be studied is the pre-requisite to an adequate structure of the leprosy control program in urban areas, the author discuss the decentralization of the data analysis with improvement of its analysis in the local lever to a better monitoring of treatment in view of the alarming number of defaulters which is themain cause of the failure of the leprosy control program; the adoption of a concept of "areas and communities with differential risk" and the concept of prevalence which, in the author's point of view, should consider only patient effectively under treatment and, additionally, that this is the best indicator to the efficiency of leprosy control programs. To the process of urbanization of the treatment the author suggests: at theindividual level : to adapt WHO-MDT treatment to fit each particular situation ( flexible supervised doses ); in the district level: to take maximum advantage of the existing basic health network for diagnosis and treatment with WHO- MDT; to identify nearby referral centers to cope with reactional cases and other ailments; to assure the participation of the general clinicians and other health personnel in the diagnosis and treatment of leprosy cases; to look for resources (knowledge and materials) in order that all news cases are properly treated with WHO-MDT; to guarantee referral for patients with disabilities; to develop an adequate and efficient information system in each area; to develop joint action with the State level; at the State level: to define focal points of coordination; to guarantee resources and drugs for treatment with WHO-MTD of all new cases; to stimulate by mass media the completion of treatment, mainly to MB cases; to guarantee the adequate treatment of disabilities; to support the development of an information system adequate to each specific area of actuation; to guarantee training and continuing education of human resources; to ascertain the the information processed in the central level reach the district level (feedback); to stimulate the delegation ofresponsibility and the participation of technical personnel in the field level; to support the local level during the transition process offering knowledge and improving practical abilities.